WGP Congress 2012 : progress in production engineering : selected, peer reviewed papers from the 2012 WGP Congress, June 27-28, 2012, Berlin, Germany (Advanced materials research ;, 2014)
Collection of selected, peer reviewed papers from the 2012 WGP Congress, June 27-28, 2012, Berlin, Germany. The 39 papers are grouped as follows: Chapter 1: Light Weight Construction, Chapter 2: Enabling Mass Production, Chapter 3: Medical and Micro Technology, Chapter 4: E-Mobility, Chapter 5: Ressource Efficiency The 39 selected and peer reviewed papers cover light weight construction, enabling mass production, medical and micro technology, electronic mobility, and resource efficiency. Among the topics are investigating the capability of flux-of-force oriented lattice structures for lightwei.